Global transcriptome profiling reveals root- and leaf-specific responses of barley (Hordeum vulgare L.) to H2O2 - Bhattacharyya, Sabarna; Giridhar, Maya; Meier, Bastian; Peiter, Edgar; Vothknecht, Ute C.; Chigri, Fatima (Frontiers in Plant Science, 2023)
In cereal crops, such as barley (Hordeum vulgare L.), the ability to appropriately respond to environmental cues is an important factor for yield stability and thus for agricultural production. Reactive oxygen species (ROS), such as hydrogen peroxide (H2O2), are key components of signal transduction cascades involved in plant adaptation to changing environmental conditions. H2O2-mediated stress responses include the modulation of expression of stress-responsive genes required to cope with different abiotic and biotic stresses. Despite its importance, knowledge of the effects of H2O2 on the barley transcriptome is still scarce. In this study, we identified global transcriptomic changes induced after application of 10 mM H2O2 to five-day-old barley plants. In total, 1883 and 1001 differentially expressed genes (DEGs) were identified in roots and leaves, respectively. Most of these DEGs were organ-specific, with only 209 DEGs commonly regulated and 37 counter-regulated between both plant parts. A GO term analysis further confirmed that different processes were affected in roots and leaves. It revealed that DEGs in leaves mostly comprised genes associated with hormone signaling, response to H2O2 and abiotic stresses. This includes many transcriptions factors and small heat shock proteins. DEGs in roots mostly comprised genes linked to crucial aspects of H2O2 catabolism and oxidant detoxification, glutathione metabolism, as well as cell wall modulation. These categories include many peroxidases and glutathione transferases. As with leaves, the H2O2 response category in roots contains small heat shock proteins, however, mostly different members of this family were affected and they were all regulated in the opposite direction in the two plant parts. Validation of the expression of the selected commonly regulated DEGs by qRT-PCR was consistent with the RNA-seq data. The data obtained in this study provide an insight into the molecular mechanisms of oxidative stress responses in barley, which might also play a role upon other stresses that induce oxidative bursts.